2019
DOI: 10.21203/rs.2.18869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinicopathologic features and genomic analysis of pulmonary blastomatoid carcinosarcoma

Abstract: Background: This study was designed to investigate the clinicopathologic features of pulmonary blastomatoid carcinosarcoma and explore the genomic profiles of epithelial and mesenchymal components in this tumor. Methods: Three cases of pulmonary blastomatoid carcinosarcoma were enrolled in this study. Clinic-pathologic information and prognostic data were retrospectively reviewed. Diagnostic immunohistochemistry was performed. The epithelial and mesenchymal components were microdissected to investigate the gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…LRP1B expression is reduced in many cancers, and it is a common mutant gene in human cancers [15][16][17]. Among the studies on LRP1B, it was found that LRP1B plays an important role and may serve as a prognostic marker for cancer during the development of various cancers including gastric cancer [18,19]. In addition, the significant associations between LRP1B mutations and TMB in lung cancer and melanoma have also been reported [15,20].…”
Section: Introductionmentioning
confidence: 96%
“…LRP1B expression is reduced in many cancers, and it is a common mutant gene in human cancers [15][16][17]. Among the studies on LRP1B, it was found that LRP1B plays an important role and may serve as a prognostic marker for cancer during the development of various cancers including gastric cancer [18,19]. In addition, the significant associations between LRP1B mutations and TMB in lung cancer and melanoma have also been reported [15,20].…”
Section: Introductionmentioning
confidence: 96%
“…Such scholarship is dominated by publications that focus on the things that are "obvious" from the eyes of global (Western) SE scholarship -from describing the models of SE (e.g., Tian et al, 2018) and the tensions in SE (e.g., Yin & Chen, 2018;Zhao & Han, 2019). Second, the Greater China SE scholarship has followed the "style and taste" of SE research in the West.…”
Section: Discussionmentioning
confidence: 99%
“…The contexts of the articles reviewed were diverse and include rural villages (Poon et al 2009), nursing homes organized by religious institutions (Zhang, 2015), post-disaster (Yu, 2016), sustainability , microfinance (Zhao & Han, 2019), elderly care homes (Wong & Tang, 2006), SE certification (Lou & Huang, 2019), work-integration social enterprises Leung et al, 2019). These diverse contexts reflect the diversity of those studied in the mainstream SE literature.…”
Section: Methodological Apparatusmentioning
confidence: 99%
See 2 more Smart Citations